LINGUAPOETIC RESEARCH OF BELLE-LETTER –DESCRIPTIVE MEANS - Shoiraxon Toshkhujayeva (Scholar Express Journal, 2021)
The Uzbek linguistics is stepping towards next empiric level of learning objective. Up to that time the scientific-theoretical evaluation to the nature of our mother tongue was scripted in several monographic, academic manuals. There is no doubt, the achievements reached are promising a great deal of possibilities from learning our national language linguistic structure into elaborate research of its event-descriptive features from all sides. Thus, scientific and practical learning the Uzbek language through up-to-date and efficient ways has been put forward as an issue on agenda. That in the world linguistics, the new direction of the practical usage of the language and its mutual attitude towards speech, society, culture, national spirituality, even the artificial intellect has been formed, challenges us to new tasks to carry out. The prosperous represemtative of modern Uzbek prose, Erkin A’zam’s fruitful creative work, is distinct and worth learning through social-phylosophic, belletristic, linguistic and lingua-poetic point of view. The reader who has read his of deeply-philosophically value and highly belletristic-sample prose works enriches his spiritual knowledge through his philosophical-belletristic skills. He shows brand-new possibilities of our mother tongue treasure, creates unexceptionally philosophical meanings and belletristic values. In Uzbek the linguistic description of events in speech judging from the linguapoetic point, that is, researching the speaker and the listener’s state and their speech condition and situation consequently gives the solution to the problems in this field. Especially, learning and researching the writer’s language details representing belle-letter style comprehension and sense as well as skills in lingua-poetic terms is a pressing issue in a globally problematic condition of nowadays’ language and its practice. The event-descriptive features of the language with its linguistic possibilities in a certain writer’s works is being learnt through the methods and methodologies on different aspects. This can be divided into three groups in Uzbek linguistics such as, learning the lexico-grammar features, learning the language units lingua-stylistically and lingua-poetically. Every writer tries to apply belletristic means to make the language of his works picturesque and impressive and so does Erkin A’zam. Simile is the subject of studies of both Literary Studies and Linguistics, in both of them it is estimated as the means of description. Using this means the writers succeed in their works being picturesque and attractive as simile is the main means, most-used in belle-letter style. The texts in the writers’ works expressing the simile is typical of the author’s or their character’s creative thinking, level, national mentality as well as lingua-cultural unit presenting the creative possibility of the language.
Keywords: linguopoetics; simile; individual speech